Clinical Manifestations of Pediatric Psoriasis: Results of a Multicenter Study in the United States. Issue 4 (30th January 2013) - Mercy, Katherine; Kwasny, Mary; Cordoro, Kelly M.; Menter, Alan; Tom, Wynnis L.; Korman, Neil; Belazarian, Leah; Armstrong, April W.; Levy, Moise L.; Paller, Amy S.
Abstract The clinical features of pediatric psoriasis warrant further attention. A national study was conducted to determine the prevalence of scalp and nail involvement and a history of guttate psoriasis at onset according to age, sex, and disease severity. One hundred eighty‐one children ages 5 to 17 years with plaque psoriasis were enrolled in a multicenter, cross‐sectional study. Subjects and guardians were asked about a history of scalp and nail involvement and whether the initial presentation was guttate. Peak psoriasis severity was assessed and defined historically as mild psoriasis (MP) or severe psoriasis (SP) according to the Physician's Global Assessment and body surface area measures. One hundred forty‐three (79.0%) subjects reported a history of scalp involvement, and 71 (39.2%) described a history of nail involvement. Boys were less likely than girls to report a history of scalp involvement (odds ratio [OR] = 0.40, 95% confidence interval [CI] = 0.19–0.84) but more likely to have had nail involvement (OR = 3.01, 95% CI = 1.62–5.60). Scalp and nail involvement was not related to psoriasis severity. In contrast, subjects with SP (35.9%) more often reported a history of guttate lesions than did those with MP (21.8%) (p = .02). Antecedent streptococcal infection was more common in children with guttate than those with plaque psoriasis at onset (p = .02) but did not correlate with severity. Sex‐related differences in scalp and nail involvement suggest koebnerization. Preceding streptococcal infection predicts guttate morphology but not severity, and initial guttate morphology is associated with eventual greater severity of disease. More aggressive monitoring and management should be considered for guttate psoriasis, given its later association with more severe disease.